THE PREFERENTIAL WELD CORROSION OF X65 CARBON STEEL PIPELINE UNDER CO2 ENVIRONMENT - Nofrizal Nofrizal; Susan A Impey; Konstantinos Georgarakis (Scientific Contributions Oil and Gas, 2019)
Preferential weld corrosion (PWC) is a severe corrosion form of attack found in pipeline weldments in oil and gas industries. PWC occurs when the corrosion rate of the weld metal (WM) and heat affected zone (HAZ) is higher than the parent metal (PM). PWC was generated by galvanic corrosion mechanism due to dissimilarities in the composition and microstructure of the metal in the three weld regions.The aim of this research is to study the effect of flow rate on preferential weld corrosion (PWC) in X65 high strength pipeline steel using submerged jet impingement by investigating the mechanism of PWC on a weldment in artificial seawater saturated with carbon dioxide at 1 bar. A novel submerged jet impingement apparatus that consist of 3 rings (outer, inner and centre) was designed so that the parent material, heat affected zone and weld metal could be analysed in a high shear stress environment. Corrosion experiments were performed with X65 pipeline steel under no flow and flowing condition at 10 m/s at 30oC and pH4. The galvanic current characteristic between the weldment regions was recorded using a zero-resistance ammeter, and the self-corrosion was analysed by using linear polarisation resistance measurements. Total corrosion rates were calculated from the sum of the galvanic and self-corrosion contributions. The morphology, structure, chemical on the surface of X65 after corrosion process was investigated by means of scanning electron microscopy (SEM) and focus ion beam (FIB) to examine the corrosion product that form in brine containing dissolved carbon dioxide.In a no-flow condition, the result shows that the galvanic characteristics on all weldments were similar and the WM is cathodic and protected in comparison with the HAZ and PM. In flowing condition, the estimated flow rates associated with the different positions on the target vary depending on either (a) PM and HAZ or (b) the WM. The effects of target flow rate on WM have a similar trend, but the overall corrosion rates are greater due to PWC. The result of surface analysis after corrosion process showing that removal of hardened layer and subsurface cracking were causes of enhanced degradation.